2014
DOI: 10.3389/fpsyg.2014.00777
|View full text |Cite
|
Sign up to set email alerts
|

Error management for musicians: an interdisciplinary conceptual framework

Abstract: Musicians tend to strive for flawless performance and perfection, avoiding errors at all costs. Dealing with errors while practicing or performing is often frustrating and can lead to anger and despair, which can explain musicians’ generally negative attitude toward errors and the tendency to aim for flawless learning in instrumental music education. But even the best performances are rarely error-free, and research in general pedagogy and psychology has shown that errors provide useful information for the lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…2,[4][5][6][7] In others, positive results of the differential learning method were not only found for training gross motor skills but also for fine motor skills, e.g., learning to play music instruments or handwriting. 8,9 However, the effect of differential learning on the development of manual skills of dental students has not previously been investigated. Therefore, the aim of this study was to evaluate if differential learning in a preclinical dental course impacted the performance of dental students in a practical exam (preparation of a gold partial crown) immediately after the training session and 20 weeks later compared to conventional learning.…”
Section: Impact Of a Differential Learning Approach On Practical Exammentioning
confidence: 99%
See 1 more Smart Citation
“…2,[4][5][6][7] In others, positive results of the differential learning method were not only found for training gross motor skills but also for fine motor skills, e.g., learning to play music instruments or handwriting. 8,9 However, the effect of differential learning on the development of manual skills of dental students has not previously been investigated. Therefore, the aim of this study was to evaluate if differential learning in a preclinical dental course impacted the performance of dental students in a practical exam (preparation of a gold partial crown) immediately after the training session and 20 weeks later compared to conventional learning.…”
Section: Impact Of a Differential Learning Approach On Practical Exammentioning
confidence: 99%
“…To allow for the self-organizing process, corrections and feedback from experts should be avoided during the exercises. 8,9 However, the effect of differential learning on the development of manual skills of dental students has not previously been investigated. In some, by including different interventions in the training sessions, the differential learning approach was more successful than the conventional training method.…”
mentioning
confidence: 99%
“…From the Latin errare, meaning to stray, "error" suggests a stepping outside of accepted boundaries. Kruse-Weber and Parncutt [22] define error in a classical music context as "unintended result of an action", and classify intended actions as those specified in the score. However, experimental electronic music performance is highly improvisational and has no vernacular resembling a classical score.…”
Section: Perception Of Error In Dmi Performancementioning
confidence: 99%
“…What varies among the performances of novices and experts is often more than simply the number of errors that occur but how quickly adjustments are made that render errors imperceptible to observers (Chen et al, 2008; Kruse-Weber & Parncutt, 2014). Chen and colleagues (2008), for example, observed that trained cellists make small positional changes in finger shape after initial contact with the string to correct the resulting pitch.…”
mentioning
confidence: 99%